Southern Highbush Blueberry Cultivars from the University of Florida - Jeffrey G. Williamson; James W. Olmstead; Gary K. England; Paul M. Lyrene (EDIS)
Many improved southern highbush cultivars have been developed by the University of Florida breeding program since the initial releases of ‘Sharpblue’, ‘Floridablue’, and ‘Avonblue’ in the mid-1970s. Today there are more blueberry cultivar choices available for Florida growers than ever before, but in every case, cultivar selection involves weighing the advantages and disadvantages of a cultivar relative to the grower’s needs. Unfortunately, there are no perfect cultivars suited for every location and management system. This 10-page fact sheet categorizes southern highbush cultivars into four groups: major cultivars, secondary cultivars, new options, and historical cultivars. Proper cultivar selection is critical to a successful blueberry enterprise, and growers should seek information from multiple sources, including their local county Extension office. Written by J.G. Williamson, J.W. Olmstead, G.K. England, and P.M. Lyrene, and published by the UF Department of Horticultural Sciences, April 2014.